2016
DOI: 10.1021/acs.inorgchem.5b02513
|View full text |Cite
|
Sign up to set email alerts
|

Compatible Mechanism for a Simultaneous Description of the Roebuck, Dushman, and Iodate–Arsenous Acid Reactions in an Acidic Medium

Abstract: The iodine-arsenous acid (Roebuck), iodide-iodate (Dushman), and iodate-arsenous acid reactions have been studied simultaneously by a stopped-flow technique by monitoring the absorbance-time profiles at the isosbestic point of the I2/I3(-) system (468 nm). Using the well-accepted rate coefficients of iodine hydrolysis, we have proven that iodine is the kinetically active species of the iodine-arsenous acid reaction. Strong iodide inhibition of this system is explained by a rapidly established equilibrium betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…10 It is therefore expected that a simpler real chemical system may facilitate the study of the theoretical background of the emergence of stochastic behavior. This expectation, along with the fact that the arsenous acid-iodate reaction exhibits crazy-clock behavior (CCB) as reported recently by our research group, 11 has led us to elucidate the comprehensive kinetic model of the arsenous acid-iodate system, 12,13 including the well-known Dushman 14 and Roebuck 15 reactions. Very recently, Pagnacco et al reported 16 that the state I (low iodide and iodine concentration) to state II (high iodide and iodine concentration) transition of the Briggs-Rauscher reaction 17 after leaving the strongly reproducible oscillatory state was found to be irreproducible as well.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…10 It is therefore expected that a simpler real chemical system may facilitate the study of the theoretical background of the emergence of stochastic behavior. This expectation, along with the fact that the arsenous acid-iodate reaction exhibits crazy-clock behavior (CCB) as reported recently by our research group, 11 has led us to elucidate the comprehensive kinetic model of the arsenous acid-iodate system, 12,13 including the well-known Dushman 14 and Roebuck 15 reactions. Very recently, Pagnacco et al reported 16 that the state I (low iodide and iodine concentration) to state II (high iodide and iodine concentration) transition of the Briggs-Rauscher reaction 17 after leaving the strongly reproducible oscillatory state was found to be irreproducible as well.…”
Section: Introductionmentioning
confidence: 83%
“…23 The concentration of the arsenite stock solution was regularly determined using a routine procedure described elsewhere. 13 All of the stock solutions were prepared from twice ionexchanged and twice distilled water. The ion-exchanged water was first distilled from potassium permanganate, then atmospherically to eliminate all carbon containing, redox active impurities from the system.…”
Section: Methodsmentioning
confidence: 99%
“…The intermediate I 2 O 2 , and its hydrated form H 2 I 2 O 3 , was proposed in 1930 by Bray (76) and has a stoichiometrically significant role in the iodide-iodate reaction mechanism in acid solution (76)(77)(78). Equilibria 32 and 33 are shifted to the right in acid solutions, although equilibrium 35, which is rapidly established, is shifted to the left even in acid solutions (79).…”
Section: áàmentioning
confidence: 98%
“…The CAPRAM-HM3.0 considers now the oxidation of HOI by ozone, 111 the OH radical, 112 H 2 O 2 , 113 and the I 2 − radical. 114 A new formation pathway is the hydrolysis of I 2 O 2 into HOI and HIO 2 , 115 which can possibly affect iodate formation as well as the lifetime of inorganic gaseous iodine.…”
Section: Acs Earth and Space Chemistrymentioning
confidence: 99%